(untitled) (Advances in Systems Science and Applications, 2010)
In this paper we derive the dynamic price model by introducing a general nonlinear form of the demand function into the traditional Cobweb model, and establish three propositions about the existence and structure stability of limit cycles by applying the qualitative theory of ordinary differential equations. The dynamic characteristics under the specific nonlinear demand function in six individual situations are discussed and illustrated by the petroleum oil daily price data from January 2 to October 27, 2009.